Is Skill-Biased Technological Change Here Yet? Evidence from Indian Manufacturing in the 1990 - Berman, Eli (World Bank, Washington, DC, 2012)
Most high and middle-income countries showed symptoms of skill-biased technological change in the 1980s. India-a low income country-did not, perhaps because India's traditionally controlled economy may have limited the transfer of technologies from abroad. However the economy underwent a sharp reform and a manufacturing boom in the 1990s, raising the possibility that technology absorption may have accelerated during the past decade. The authors investigate the hypothesis that skill-biased technological change did in fact arrive in India in the 1990s using panel data disaggregated by industry and state from the Annual Survey of Industry. These data confirm that while the 1980s were a period of falling skills demand, the 1990s showed generally rising demand for skills, with variation across states. They find that increased output and capital-skill complementarity appear to be the best explanations of skill upgrading in the 1990s. Skill upgrading did not occur in the same set of industries in India as it did in other countries, suggesting that increased demand for skills in Indian manufacturing is not due to the international diffusion of recent vintages of skill-biased technologies.